Madagascar’s wildfowl (Anatidae) in the new millennium - Young, H. Glyn; Razafindrajao, Félix; Lewis, Richard E (Wildfowl, 2013)
Ten wildfowl taxa are resident in Madagascar including four endemics: Madagascar White-backed Duck Thalassornis leuconotus insularis, Madagascar Teal Anas bernieri, Meller’s Duck A. melleri and Madagascar Pochard Aythya innotata. These endemic duck taxa were amongst the last wildfowl forms to be described in Africa and are undoubtedly currently the rarest in this region. The history of our knowledge of these birds follows four easily definable stages: discovery, understanding, protection and the future. The new millennium has started with a much more detailed understanding of the four ducks’ ecology than ever before, the protection of several key sites and the re-discovery in 2006 of the Madagascar Pochard. The next few years will tell if the ducks have a more secure future and, while not yet safe, Madagascar’s ducks are perhaps now among the better known of Africa’s endemic wildfowl.